INOVASI PENINGKATAN PAJAK DAERAH DI KABUPATEN SUMBA TIMUR - Jainal Abdullah Bengkari (Jurnal Administrasi Publik, 2023)
Regional taxes are still the main support as a source of local revenue in East Sumba Regency, but the implementation is not as expected. The development of regional original income from 2017 to 202 always experienced an insignificant increase and in 2020 it decreased. In the current era of the industrial revolution 4.0, technology-based tax management is a new breakthrough to avoid tax evasion and minimize fraud in tax payments by taxpayers. Conventional tax collection can lead to opportunities for misappropriation of the amount of tax revenue and a long implementation time because it requires more and more competent human resources. Therefore, local tax management by utilizing information technology can streamline several local government revenue sources from local tax sector revenues such as hotel taxes, restaurant taxes and entertainment taxes. The results of the study show that the application of Sustaining innovation by BAPENDA has gone well, namely the use of the PBB SIP, BPHTB SIP and SIMPATDA applications. But in Disruptive Innovation, the use of tapping box tools installed in hotels and restaurants did not work as expected because an error occurred from the planning to the implementation process.